PENINGKATAN HASIL BELAJAR BUDAYA ALAM MINANGKABAU (BAM) PESEERTA DIDIK MELALUI PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DI KELAS VIII SMPN SATU ATAP SALIMPAUNG - FAKHRIZAL, Drs. Eswendi,M.Pd, Dr. Yahya, M.Pd (Serupa The Journal of Art Education, 2015)
Learning Culture Minangkabau (BAM) tend to be static and monotonous, so that students are less motivated to be active in the study, which resulted in poor learning outcomes obtained. Among the causes are the teachers teaching method not only recruit dynamic and lecture model. Another factor is the interest and motivation of learners itself is low and also contributed to the low activity and learning outcomes. Therefore, we need a model of learning that can spur activity and learning outcomes of students BAM is to implement cooperative learning make a match.This study is a classroom action research with two cycles. The subjects were students of class VIII SMP Salimpaung One Roof. Researchers working with colleagues as an observer (observer). Data were collected through observation result sheet peers and the results of the study before and after the action. Processing data using the t test and the percentage techniques in view of the tendency of the data after performing the action.Research shows that the use of cooperative learning methods Make a Match can improve learning outcomes. It can be seen from the average value of 69.7 pre-cycle, the first cycle increased to 72.95, and the second cycle increased to 76.9. Classical completeness before action was 27.2%, in the first cycle increased to 59%, and the second cycle increased to 77.2%, which exceeds the indicators of success set at 76%. To prove the hypothesis t test. From the t-test results can be seen in figures the probability (sig) is 0.003 and the t -3395. Thus learning methods make a match can improve learning outcomes of students in class VIII SMP Salimpaung One Roof. Based on t-test probability of figures (sig) ≤ 0.003 0.005 then the hypothesis can be accepted.Keywords: learning outcomes, Culture, Cooperative, Make a Match